Cerebellar liponeurocytoma in two siblings suggests a possible familial predisposition. (October 2016) - Pikis, Stylianos; Fellig, Yakov; Margolin, Emil
Highlights: The molecular biology and genetic origin of cerebellar liponeurocytomas is yet to be defined. Cerebellar liponeurocytomas afflicting multiple members of the same family has been recently reported. The existence of a germline mutation predisposing only to cerebellar liponeurocytoma has been recently suggested. Abstract: There is limited data on the genetic origin and natural history of cerebellar liponeurocytoma. To the best of our knowledge there has been only one report of a familial presentation of this rare entity. We report a 72-year-old female with a posterior fossa tumor presenting with progressive cerebellar signs and symptoms. The patient underwent total tumor resection via an uncomplicated sub-occipital craniotomy. Histopathologic examination was diagnostic for cerebellar liponeurocytoma. Her sister was previously treated for a similar tumor. Our report provides further evidence for the possible existence of a hereditary abnormality predisposing afflicted families to cerebellar liponeurocytoma development.